Performance of wheat genotypes at different dates of sowing under irrigated conditions - Shroti, S.K.; Chauhan, S.K. (Annals of Agricultural Research, 2016)
A field experiment was conducted at Nidhauli Kalan, Etah, during the Rabi season of 2009-10 to find high yielding genotype of wheat with suitable sowing time. Research indicated that when the sowing was delayed from normal to late (December 12th) and very late (January 2nd), the biological yield was reduced to the tune of 7.0 and 13.2%, respectively. The increase in grain yield with normal sowing was 22.7% and 45.6% when compared with late and very late sowing especialy. Genotype HD-2985 was significantly higher seed yield as compared to all other genotypes. Genotype PBW-343 suspected in higher grain yield by 8.88 and 23.75% over rest of the genotypes. Highest the net return of Rs. 41990.7 ha–1 and B:C ratio of 2.0 were obtained with wheat genotype HD 2985 when sown at normal time (18th November).